PLANNING OF A SEWERAGE SYSTEM FOR SEMI-CENTRALIZED SCALE IN HIGH OPEN DEFECATION NEIGHBOURHOOD AT KAMPUNG MELAYU VILLAGE, EAST JAKARTAOOD AT KAMPUNG MELAYU VILLAGE, EAST JAKARTA - Jairus Stefanus, Kevin
Based on data from STBM (2021) that currently residents in Kampung Melayu Village, East Jakarta still have open defecation (OD) as many as 6182 families or 80.2% of the total residents in Kampung Melayu Village. In general, the high rate of OD in this area is caused by the fact that the majority of the community immediately directs their wastewater into the drainage canal. Others already had a Tangki septik, but rarely or never did suck stool. The absence of proper domestic wastewater treatment could cause environmental pollution and health problems for the surrounding community. Therefore, it was necessary to plan a domestic wastewater management system for the Kampung Melayu Village on a semi-centralized scale. As for planning, there were several systems consisting of individual tangki septiks, communal tangki septiks, and communal WWTP. In planning this final project, the author only focuses on the sewerage system at the Communal WWTP in Kampung Melayu Village. In this plan, there were two systems consisting of IK 217 SR and IK 340 SR. The two systems are planned to have each of two alternative pipeline networks with alternative selection carried out using the Simple Additive Weighting (SAW) method. The planning results for both systems were obtained using a Shallow Sewerage system with gravity flow. The type of pipe planned in the system uses PVC Class VU (D) with a diameter ranging from 4 – 5 inches. From the planning results, it was also found that the pipe will be planted in the excavation around 0.28 – 1.6 m with a slope of 0.001 – 0.116 for IK 217 SR and 0.54 – 3.841 m with a slope of 0.0006 – 0.112 for IK 340 SR.